Ti3C2Tx/MoO3 composite as saturable absorber for dissipative soliton 1.0 μm mode-locked fiber laser - Ahmad, Harith; Lutfi, M.A.M.; Zaini, Muhammad Khairol Annuar; Samion, Muhamad Zharif; Sagadevan, Suresh; Ortaç, B.; Thambiratnam, Kavintheran (Institute of Physics, 2025)
This work demonstrated a passive mode-locked ytterbium-doped fiber laser operating at a 1-micron region. The saturable absorber incorporated was a Ti3C2Tx/MoO3 deposited on a D-shaped fiber, generating stable dissipative soliton in all normal dispersion regimes. The all-fiber ring cavity laser configuration generates mode-locked pulses with a repetition rate of 24.2 MHz, which was further verified on the radio frequency spectrum. The dissipative soliton spectrum was centered explicitly at 1031 nm with a spectral edge-to-edge bandwidth of ∼3.7 nm. The Ti3C2Tx/MoO3 saturable absorber provides mode-locked stability with ∼59 dB of signal-to-noise ratio. The Ti3C2Tx/MoO3 mode-locked laser was amplified up to 101 mW, corresponding to 4.1 nJ of single pulse energy. © 2025 The Author(s). Published by IOP Publishing Ltd.